Control points deployment in an Intelligent Transportation System for monitoring inter-urban network roadway - Martin Luther Mfenjou; Ado Adamou Abba Ari; Arouna Ndam Njoya; David Jaures Fotsa Mbogne; Kolyang; Wahabou Abdou; François Spies (Journal of King Saud University: Computer and Information Sciences)
The constant evolution of transportation systems and traffic in developing countries is nowadays confronted with a problem of road safety and therefore of a high accident rate, especially in the context of inter-urban road transport. In this work, we propose a communication architecture for an Intelligent Transport System (ITS) to provide surveillance in an inter-urban transport network in the context of developing countries. We introduce two types of control points: Relay Control Points (RCP) and Treatment Control Points (TrCP). We also designed two multi-objective models for the deployment of these points. In order to ensure good coverage, to minimize the cost of installation and to put more emphasis in the areas having a high number of accidents. To ensure optimal deployment of these points, we have used the Non-Dominated Sorted Genetic Algorithm II (NSGA-II) that will allow to realize the Pareto front of non-dominated solutions. The results of the simulations show the effectiveness of our proposal.